2023
DOI: 10.3390/nu15234878
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of American Ginseng Stems and Leaves by an Endophytic Fungus Umbelopsis sp. and Its Effect on Alzheimer’s Disease Control

Qiqi Chen,
Jingying Wang,
Yuhang Gao
et al.

Abstract: Background: Common ginsenosides can be transformed into rare ginsenosides through microbial fermentation, and some rare ginsenosides can prevent Alzheimer’s disease (AD). This study aimed to transform common ginsenosides into rare ginsenosides through solid-state fermentation of American ginseng stems and leaves (AGSL) by an endophytic fungus and to explore whether fermented saponin extracts prevent AD. Methods: The powders of AGSL were fermented in a solid state by endophytic fungus. Total saponins were extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Ginseng has the capacity to scavenge free radicals because it contains polysaccharides [49], polyphenols [50], flavonoids, ginsenosides [51], and other active The reason for the changes in the concentration and type of saponins was that glucose groups at the C 6 and C 20 positions of the protopanaxatriol (PPT) saponin and the C 3 and C 20 positions of the ginsenosides of the protopanaxadiol saponin were hydrolyzed during the fermentation process, resulting in rare ginsenosides [45]. Palaniyandi et al [9] showed that Rb 1 /Rb 2 glycol saponins are transformed by microorganisms to generate Rd, and Rd can then be further converted to Rg 3 , Rh 2 , F 2 , and CK.…”
Section: Correlation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Ginseng has the capacity to scavenge free radicals because it contains polysaccharides [49], polyphenols [50], flavonoids, ginsenosides [51], and other active The reason for the changes in the concentration and type of saponins was that glucose groups at the C 6 and C 20 positions of the protopanaxatriol (PPT) saponin and the C 3 and C 20 positions of the ginsenosides of the protopanaxadiol saponin were hydrolyzed during the fermentation process, resulting in rare ginsenosides [45]. Palaniyandi et al [9] showed that Rb 1 /Rb 2 glycol saponins are transformed by microorganisms to generate Rd, and Rd can then be further converted to Rg 3 , Rh 2 , F 2 , and CK.…”
Section: Correlation Analysismentioning
confidence: 99%
“…The liquid chromatography-mass spectrometry ion source operating parameters were as follows: Electrospray ion source (ESI) was used, the scanning mode was positive and negative ion switching, the multiple reaction monitoring mode was used for detection, the atomized gas flow was 3.0 L/min, the drying gas flow was 10.0 L/min, the heating gas flow was 10 L/min, the connection temperature was 300 • C, the desolvation line was at 250 • C, the heating block temperature was 400 • C, and the collision-induced dissociation pressure was 270 kPa. The following three factors were varied with the aim of increasing the antioxidant activity of the fermentation products: fermentation time (15,30,45,60, and 75 h), fermentation temperature (26,28,30,32, and 34 • C), and inoculum size (1.5, 2.0, 2.5, 3.0, and 3.5% v/v). The selection of time, temperature, and inoculum size as the main factors for process optimization was based on the method proposed by Tao et al [75].…”
Section: Ginsenoside Monomer Quantificationmentioning
confidence: 99%
“…In our previous research, extracts obtained from a liquid medium of potato dextrose (PD) fermented by an endophytic fungus strain NSJG isolated from wild ginseng could produce total saponins. The strain NSJG was identified as Umbelopsis dimorpha [31]. This study optimized the medium and fermentation conditions to enhance total saponin production and identified saponin styles in fermentation extracts.…”
Section: Introductionmentioning
confidence: 99%